Does opportunism pay off? - Veiga, Linda Gonçalves (2006)
This article tests the hypothesis that the opportunistic manipulation of financial accounts by mayors increases their chances of re-election. Working with a large and detailed dataset comprising all Portuguese mainland municipalities, which covers the municipal elections that took place from 1979 to 2001, we clearly show that increases in investment expenditures and changes in the composition of spending favouring highly visible items are associated with higher vote percentages for incumbent mayors seeking re-election. Our results also indicate that the political payoff to opportunistic spending increased after democracy became well-established in the country.